2019
DOI: 10.3390/cancers11040458
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cell-Free DNA and RNA Analysis as Liquid Biopsy: Optimal Centrifugation Protocol

Abstract: The combined analysis of circulating cell-free (tumor) DNA (cfDNA/ctDNA) and circulating cell-free (tumor) RNA (cfRNA/ctRNA) shows great promise in determining the molecular profile of cancer patients. Optimization of the workflow is necessary to achieve consistent and reproducible results. In this study, we compared five centrifugation protocols for the optimal yield of both cfDNA/ctDNA and cfRNA/ctRNA. These protocols varied in centrifugation speed, ambient temperature, time, and number of centrifugation ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 36 publications
4
54
1
Order By: Relevance
“…State‐of‐the‐art updates on technologies and clinical applications of liquid biopsy, including the abovementioned CTCs, ctDNA, ctRNA, microvesicles, and single‐cell sequencing, hold the prospects for anticancer drug development, individualized treatment on cancer patients, and tumor risk assessment in general population (Anfossi et al, 2018; Best et al, 2015; Osumi et al, 2019; Sorber et al, 2019; Wang & Chen, 2014, Xu et al, 2018). Of them, CTCs recognized as the precursors of metastasis and the dissemination in patients’ bloodstream are involved in metastatic and recurrent cancers (Keller & Pantel, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…State‐of‐the‐art updates on technologies and clinical applications of liquid biopsy, including the abovementioned CTCs, ctDNA, ctRNA, microvesicles, and single‐cell sequencing, hold the prospects for anticancer drug development, individualized treatment on cancer patients, and tumor risk assessment in general population (Anfossi et al, 2018; Best et al, 2015; Osumi et al, 2019; Sorber et al, 2019; Wang & Chen, 2014, Xu et al, 2018). Of them, CTCs recognized as the precursors of metastasis and the dissemination in patients’ bloodstream are involved in metastatic and recurrent cancers (Keller & Pantel, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CTCs in combination with other liquid biopsy technologies such as circulating tumor DNAs, microRNAs and noncoding RNAs (ctDNA, ctRNA), tumor‐educated platelets, extracellular vesicles, or even with single‐cell technologies have contributed to uncover cancer heterogeneity and hold the promise for providing unique insights into genomic aberrations as well (Anfossi et al, 2018; Best et al, 2015; Osumi et al, 2019; Sorber et al, 2019; Wang & Chen, 2014; Xu et al, 2018). For instance, we recently reported the genome‑wide pattern differences in copy number variations (CNVs) of CTCs in breast cancer patients with liver metastasis (Zou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that interventional therapies may influence the expression levels of hsa_circ_0003056 in the plasma. circRNAs are relatively stable in plasma, however, the total free nucleic acid content of the peripheral blood is low (28). There are no stable, internal or precise quantification methods for the determination of these levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended to perform plasma isolation soon after blood withdrawal, while inappropriate handling and storage leads to non-informative liquid biopsy samples due to leukocyte lysis and therefore contamination with genomic DNA [ 13 , 14 , 15 ], thereby leading to non-suitable therapeutic options and treatment failure of those inappropriately handled samples [ 16 ]. Further, the usage of different blood collection tubes and centrifugation protocols for plasma isolation might cause a contamination of the plasma samples with high molecular genomic DNA to variable degrees [ 17 , 18 , 19 , 20 ]. However, how to use those non-appropriate handled liquid biopsy samples for further NGS approaches and how to rescue ctDNA from those samples remains a matter of debate.…”
Section: Introductionmentioning
confidence: 99%